2008
DOI: 10.1063/1.2966370
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetic-algorithm and emissivity-ratio analyses of image data from OMEGA implosion cores

Abstract: Detailed analysis of x-ray narrow-band images from argon-doped deuterium-filled inertial confinement fusion implosion experiments yields information about the temperature spatial structure in the core at the collapse of the implosion. We discuss the analysis of direct-drive implosion experiments at OMEGA, in which multiple narrow-band images were recorded with a multimonochromatic x-ray imaging instrument. The temperature spatial structure is investigated by using the sensitivity of the Ly beta/He beta line em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
(10 reference statements)
0
26
0
Order By: Relevance
“…argon Heb and Lyb) of the four frames in the MMI gated data with the time-histories of the same line emission recorded with a streaked spectrometer. 17 For the purpose of volume determination, "simultaneous" is defined as Dt max  v imp < Dx instrum , where Dt max is the maximum time difference between data recorded along different lines of sight, v imp is the shell implosion velocity, and Dx instrum is the spatial resolution of the instrument. For the particular shot that we have been discussing, we found that frame 3 of TIM3, TIM4, and TIM5 have times close enough to apply the volume determination algorithms discussed here.…”
Section: Core Volume Shape and Size Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…argon Heb and Lyb) of the four frames in the MMI gated data with the time-histories of the same line emission recorded with a streaked spectrometer. 17 For the purpose of volume determination, "simultaneous" is defined as Dt max  v imp < Dx instrum , where Dt max is the maximum time difference between data recorded along different lines of sight, v imp is the shell implosion velocity, and Dx instrum is the spatial resolution of the instrument. For the particular shot that we have been discussing, we found that frame 3 of TIM3, TIM4, and TIM5 have times close enough to apply the volume determination algorithms discussed here.…”
Section: Core Volume Shape and Size Estimationmentioning
confidence: 99%
“…[3][4][5][6] The ideal implosion requires spherically symmetric compression, which is hard to achieve due to laser nonuniformity, laser power imbalance, and surface roughness amplified by various hydrodynamic instabilities. To study the symmetry and spatial structure of the compressed core, various imaging instruments have been developed including the gated monochromatic x-ray imager, 7,8 monochromatic x-ray imaging with bent crystals, [9][10][11] and multimonochromatic x-ray imager (MMI) applied to indirect-drive, [12][13][14][15] and direct-drive 16,17 laser-driven implosions. Monochromatic images (or narrowband images) show core images of specific line transitions from spectroscopic tracers, which have potential to unveil the spatial structure of temperature and density in the core.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we extracted timeresolved 2D T e maps from two narrow-band images [11] . From a collection of space-resolved spectra, we extracted time-resolved 2D T e and n e maps [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The optical depths of Heβ and Lyβ are small; still neglecting the opacity effects in the level population kinetics and in the emergent spectra calculation would not produce the most accurate analysis results [14,15]. The opacity effect in the level population kinetics is important to compute reliable plasma emissivity and opacity.…”
mentioning
confidence: 99%
“…The ratio of the two narrow-band images, Lyβ to Heβ, is related to the temperature spatial structure [15]. Thus, another way to define sub-region masks is based on the contour levels of the Ar Lyβ to Heβ ratio image.…”
mentioning
confidence: 99%